Estimating age at death from an archaeological bone sample – a preliminary study based on comparison of histomorphometric methods - Mnich, Barbara; Skrzat, Janusz; Szostek, Krzysztof (Anthropological Review, 2017)
The estimation of age at death is one of the most fundamental biological parameters, determined on skeletal remains in anthropological context. That is why, there is a constant need to improve applied methods. Histomorphometry, which uses microscopic analysis of bone tissue is suggested to be one alternative method. In general, this technique is based on measurements and the determination of the number and density of basic bone structural units, osteons. Osteon density is found to be related with age of the individual. The main goal of this research was to compare results of determined age at death, on the basis of ribs histology, comes from methods proposed by different authors. We analyzed ground cross sections of ribs from archeological origin. The presented methodology is simple in use and effective. Four different methods were tested (Stout and Paine 1992; Cho et al. 2002; Kim et al. 2007; Bednarek et al. 2009). The obtained age results were compared with each other as well as related to the age estimated by standard macroscopic method used in anthropology. Bednarek’s method is recognized to be the most supportive for anthropological analyzes. Methodological issues connected with grinding methodology and results interpretation are also presented. Hypothesis about interpopulation as well as histological and dimorphic differences were confirmed.